2000
DOI: 10.1111/j.1741-3729.2000.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult Children and Grandchildren in Primary Caregiver Roles to Older Relatives and Their Service Needs

Abstract: Expansion of the family to four generations has resulted in a new population of caregivers to elderly members: young adults. Our study provides both quantitative and qualitative findings on children and grandchildren (N ϭ 43), aged 40 years and younger, serving as the major source of support to an older relative(s). Intervention strategies for professionals in direct contact with this age group are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
126
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(135 citation statements)
references
References 23 publications
7
126
0
1
Order By: Relevance
“…In line with prior studies of young adult caregivers and college caregivers [6][7][8], it was hypothesized that college caregivers would endorse greater symptoms of depression and distress [7][8] and report lower grade point averages than non-caregiving peers.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…In line with prior studies of young adult caregivers and college caregivers [6][7][8], it was hypothesized that college caregivers would endorse greater symptoms of depression and distress [7][8] and report lower grade point averages than non-caregiving peers.…”
Section: Introductionmentioning
confidence: 58%
“…Their marginally lower grade point averages may reflect the cumulative impact of managing multiple demands on their time, cognitive and physical energy, and coursework. Other studies of young caregivers have shown caregiving to be associated with fatigue [6], missed time from school, academic withdrawal [15,16], difficulty adjusting to college [8], declines in academic achievement [4], and difficulty with maintaining social relationships [7]. Alternatively, non-caregivers may come from families where other members have assumed caregiving roles or they may prioritize educational attainment over fulfillment of caregiving roles.…”
Section: Demographic Differencesmentioning
confidence: 99%
See 3 more Smart Citations